But I Don’t Understand You: One Faculty’s Observations of the Challenges Facing International Healthcare Students - DuBose, Cheryl O. (Journal of International Students, 2017)
International students face many challenges when pursuing a degree in higher education. Communication and cultural differences are typically cited as the most challenging aspects of any study abroad program. Students attempting to complete a healthcare program face sometimes insurmountable issues, as communication, cultural differences, and discrimination play a large role in providing quality patient care. This paper is a commentary on my experiences as a faculty member with various international students enrolled in healthcare programs in the southeastern United States.